2022
DOI: 10.1038/s41598-022-17099-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in storm surge climate derived from an ensemble of global surge reconstructions

Abstract: We address the challenge, due to sparse observational records, of investigating long-term changes in the storm surge climate globally. We use two centennial and three satellite-era daily storm surge time series from the Global Storm Surge Reconstructions (GSSR) database and assess trends in the magnitude and frequency of extreme storm surge events at 320 tide gauges across the globe from 1930, 1950, and 1980 to present. Before calculating trends, we perform change point analysis to identify and remove data whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We are not aware of previous global estimates of storm surge trends from model data. Although, Tadesse et al 23 did determine storm surge trends at tide gauge locations concentrated in western Europe, North America, Japan and southern Australia. Their findings 23 (see their Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of previous global estimates of storm surge trends from model data. Although, Tadesse et al 23 did determine storm surge trends at tide gauge locations concentrated in western Europe, North America, Japan and southern Australia. Their findings 23 (see their Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although, Tadesse et al 23 did determine storm surge trends at tide gauge locations concentrated in western Europe, North America, Japan and southern Australia. Their findings 23 (see their Fig. 5 ) are generally consistent with the present results.…”
Section: Resultsmentioning
confidence: 99%
“…Extreme significant wave heights are projected to be significantly larger (up to +40%) at the end of the century under the SSP5-8.5 scenario due to the consideration of mean SLR and tides (Arns et al, 2017;Chaigneau et al, 2023) with implications on wave setup and runup and thus on projections of ESLs. In addition, recent studies have shown, on a global scale and more specifically for Europe, that historical trends in storm surges (Calafat et al, 2022;Reinert et al, 2021;Roustan et al, 2022;Tadesse et al, 2022) and tides (Pineau-Guillou et al, 2021) have been comparable in magnitude to the historical mean SLR trend.…”
Section: Projections Of Dynamic Changes In Extremesmentioning
confidence: 96%
“…Alternatively, data-driven models can be used to generate an ensemble (e.g. Tadesse and Wahl, 2021;Tadesse et al, 2022). However, these data-driven models are only applicable to gauge stations.…”
Section: Introductionmentioning
confidence: 99%